Coded Random Access Technique Based on Repetition Codes for Prioritizing Emergency Communication - Khoirun Ni'amah; Solichah Larasati; Alfin Hikmaturokhman; Muntaqo Alfin Amanaf; Achmad Rizal Danisya (Buletin Pos dan Telekomunikasi, 2020)
This research uses repetition codes based on Coded Random Access (CRA) to support Internet of Things (IoT) to give priority to emergency commutations in super-dense networks. Degree distribution for emergency group and general group are obtained with extrinsic information transfer (EXIT) analysis to achieve small error performance shown by the very small gap between emergency group curve and general group curve. This research also evaluates performance by observing throughput and packet-loss rate (PLR) parameters from every groups. Offered traffic in PLR  for emergency group user is G= 0,7 packet/slot without fading and G= 0,65 packet/slot with fading, while for public group is G=0,699 packet/slot without fading and G=0,42 packet/slot with fading. Peak throughput for emergency group is G= 0,737 packet/slot without fading and G= 0,729 packet/slot with fading. Peak Throughput for public group is G= 0,699 packet/slot without fading and G=0,685 packet/slot with fading. Throughput values of emergency group are higher than those of the general group, indicating successful process of giving priority for emergency group.